SENAM ERGONOMIK UNTUK EFIKASI DIRI DAN ASAM URAT PENDERITA GOUT ARTRITIS - Anggoronggang, Gift; Rakinaung, Natalia; Oroh, Cindi (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Introduction: Non-infectious degenerative diseases such as gout arthritis usually last a long time and are often found in young people and the elderly. Self-efficacy can be defined as belief in one’s ability to perform a task with the desired result. Ergonomic exercise is given 3 times a week to patients with gout arthritis as a non-pharmacological therapy to reduce uric acid levels. Objective: To determine the effectiveness of ergonomic exercise on Self-efficacy and uric acid levels in gout arthritis sufferers in Tateli Tiga Village, Mandolang District, Minahasa District. Method: This study used a quasy experiment with a one group pretest-posttest design. The population of gout arthritis sufferers at the Tateli Health Center and the people of Tateli Tiga Village, Mandolang District, Minahasa Regency is 68 people. The sampling technique used is total sampling. Analysis using the Wilcoxon test. Results: The result of the analysis using the Wilcoxon test on uric acid levels before and after the intervention obtained a p-value of 0,000 (<0,05), and for Self-efficacy the results obtained a p-value of 0,000 (<0,05). Conclusions: There is a difference between ergonomic exercise on Self-efficacy and uric acid levels in gout arthritis sufferers before and after being given ergonomic exercise.